Development Of Job Vacancy Information Services Through the Mobile JOBPOINT Application - Aziz, Azzam Bilal Abdul; Wiranatakusuma, Dimas Bagus (Universitas Muhammadiyah Yogyakarta, 2023)
The purpose of this research is to create a job information provider service using the Jobpoint mobile application in the context of the digital economy. This study examines the impact of advances in information and communication technology on communication methods and acceleration of business processes. through the Jobpoint mobile application and offers insights and alternative solutions for the development of job vacancy information. The research methodology involved a literature review and the development of the Jobpoint mobile application, which included a needs analysis, design, implementation, and testing phase. The result of this research is the creation of the Jobpoint mobile application which allows job seekers to access company profiles, communicate directly with recruiters and companies, send resumes, and find job vacancies according to their interests. This application is expected to increase job seekers' access to job vacancy information and make it easier for them to find and apply for jobs.